Reflections on change theory and community-based participatory action research: congruent, similar or different? - Asirifi, Mary; Ogilvie, Linda; Barton, Sylvia; Bilash, Olenka; Stobart, Kent; Aniteye, Patience; Kwashie, Atswei (My University, 2022)
While change is acknowledged as integral to all action research, literature linking the theories of change theoretically merits exploration. Are some theories of change more congruent to principles of action research than others? Does congruence depend on which type of action research and which change theory are being compared? During the implementation of a four-cycle community-based participatory action research (CBPR) project in nursing education in Ghana, such questions arose. This paper is an attempt to grapple with those questions. While Kotter’s eight-step theory of organizational change was chosen to guide this study, it became obvious that various elements of change theories were integrated in the study as it progressed. For Kotter’s organizational change theory to serve as an effective guide for the implementation cycles in the CBPR project, it must be conducted through the lens of critical social theory and a perspective on social and cultural change.
Keywords: change; community-based participatory action research; Ghana; nursing education